The Application and Impact of Video-Based Fairy Tales on Students’ Communication Skills at a State Islamic Elementary School - Lydia Al-Hudzaifah (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Language is a system of verbal symbols agreed upon by a community for communication and interaction, grounded in a shared culture. In instruction, relevant strategies are needed to strengthen students’ communication skills. Objective: To determine the effect of applying the storytelling (fairy-tale) method through video media on communication skills in Indonesian language learning for second-grade students at MIN 1 Bengkulu City. Method: A quasi-experimental design was employed with 26 second-grade students at MIN 1 Kota Bengkulu, as participants. The intervention consisted of Indonesian language lessons using a storytelling method supported by video media. Result: Findings indicate that the application of storytelling through video media has a positive effect on students’ communication skills in Indonesian language learning. Conclusion: The conclusion reveals that video-assisted storytelling is a worthwhile consideration as an alternative learning strategy to enhance the communication skills of elementary school students. Contribution: This study provides empirical evidence on the effectiveness of storytelling through video media in the context of Indonesian language learning in elementary schools, offering practical insights for teachers and informing curriculum design.